(untitled) (CIPEEX, 2025)
Burnout Syndrome is a psychological disorder characterized by physical and emotional exhaustion resulting from stressful work situations. Recognized by the World Health Organization (WHO) as an occupational condition, it affects the health and quality of life of professionals, compromising work performance and personal life. This study explores the impacts of Burnout Syndrome in the workplace, its main causes and discusses strategies for preventing and managing the problem. Burnout manifests itself in three dimensions: emotional exhaustion, depersonalization and low professional achievement. Affected professionals feel constantly tired, develop a cynical attitude towards work and interactions with colleagues and clients, and often believe that their performance is inadequate. These symptoms are common in professions that require high levels of human interaction and responsibility, such as health professionals, educators, managers and frontline workers. The causes of Burnout Syndrome include work overload, pressure for results, lack of organizational support and toxic work environments. A corporate culture that values long working hours and neglects employee well-being is an aggravating factor. Technology also contributes, as hyperconnectivity makes it difficult for professionals to disconnect from work, even outside of working hours. The lack of balance between personal and professional life, added to the feeling of lack of control over tasks, intensifies vulnerability to the syndrome. The impacts of Burnout affect both the individual and the organization. On a personal level, it can lead to physical and mental health problems, such as insomnia, depression, anxiety and cardiovascular diseases. In the organizational context, it results in increased absenteeism, high turnover, a drop in productivity and high costs for sick leave and medical treatment. This scenario highlights the need for companies to recognize Burnout as a problem that requires preventive action. Preventing Burnout Syndrome requires an integrated approach involving individuals and organizations. Companies should promote a healthy work culture, valuing work-life balance and setting clear limits on workload. Psychological support programs, stress management training and wellness initiatives, such as regular breaks and flexible hours, help mitigate burnout. Leaders and managers should offer support and create an empathetic and welcoming work environment. For individuals, self-care strategies are essential. Maintaining a healthy routine with exercise, a balanced diet and moments of leisure and rest is crucial. Setting limits, delegating tasks and seeking professional help are practices that help prevent and treat burnout. In conclusion, Burnout Syndrome is a consequence of dysfunctional work environments and must be addressed seriously. Investing in promoting the mental health and well-being of employees is